Determinants of Human Papillomavirus Vaccination Intention Among Female Sex Workers in Amsterdam, the Netherlands. Issue 12 (December 2017) - Marra, Elske; van Dam, Laura; Kroone, Niki; Craanen, Marianne; Zimet, Gregory D.; Heijman, Titia; Hogewoning, Arjan A.; Sonder, Gerard J.B.; de Vries, Henry J.C.; Alberts, Catharina J.; Paulussen, Theo G.W.M.; Schim van der Loeff, Maarten F.
Abstract : Introduction: Female sex workers (FSWs) are at risk for human papillomavirus (HPV)–induced diseases but are currently not targeted by the HPV vaccination program in the Netherlands. We explored determinants of their intention to get vaccinated against HPV in case vaccination would be offered to them. Methods: In 2016, FSWs 18 years and older having a sexually transmitted infection consultation with the Prostitution & Health Center (P&G292) in Amsterdam, either at the clinic or at their working location, were invited to complete a questionnaire assessing sociopsychological determinants of HPV vaccination intention (scale ranging from −3 to +3). Determinants of HPV vaccination intention were assessed with univariable and multivariable linear regression. In addition, we explored the effect of out-of-pocket payment on intention. Results: Between May and September 2016, 294 FSWs participated. The median age was 29 years (interquartile range, 25–37 years). Human papillomavirus vaccination intention was high (mean, 2.0; 95% confidence interval [CI], 1.8–2.2). In multivariable analysis, attitude ( β = 0.6; 95% CI, 0.5–0.7), descriptive norm ( β = 0.2; 95% CI, 0.1–0.3), self-efficacy ( β = 0.2; 95% CI, 0.1–0.3), beliefs ( β = 0.1; 95% CI, 0.0–0.2), and subjective norm ( β = 0.1; 95% CI, 0.0–0.2) seemed to be the strongest predictors of HPV vaccination intention ( R 2 = 0.54). Human papillomavirus vaccination intention decreased significantly to a mean of 0.2 when vaccination would require out-of-pocket payment of [Euro sign]350. Conclusions: The HPV vaccination intention among FSWs seems relatively high and is most strongly constituted in attitudinal, normative, and self-efficacy beliefs. Out-of-pocket payment will probably have a negative impact on their HPV vaccination acceptability. Abstract : We assessed human papillomavirus vaccination intention among female sex workers in Amsterdam. Intention was high and was explained by attitudinal, normative, and self-efficacy beliefs. Required payment had a negative impact. Supplemental digital content is available in the text.